Marginalization and exclusion as socio-economic factors of urban violence: the case of Valle de Chalco Solidaridad, Estado de México - López-Santiago, Marco Andrés; Hernández-Juárez, Martín; León-Merino, Aurelio (Papeles de Población; Vol. 23 Núm. 91 (2017), 2017)
This paper shows the results of research related to socio-economic factors that influence the emergence of violence in the municipality of Valle de Chalco Solidaridad, Estado de México. A mixed study method was used which included both quantitative and qualitative variables. Official databases, key informants interviews and focus groups discussions were used in this study. It was concluded that, along with other factors, socio-economic marginalization, unemployment, fall in wages and income provoke discontent and frustration among the population, resulting in diverse forms of violence in the municipality.